Acoustic performance in residential buildings - still in 2022 construction companies have not adequate the application of the ABNT-NBR 15575 standard - Resende, Lucas Marques (2022)
This article aims to objectively point out the main difficulties encountered by construction companies to follow the     requirements of NBR 15575, about acoustic performance, which has become a parameter for the execution of projects executed from July 19, 2013. The study concluded that one of the obstacles encountered in putting this standard into practice, efficiently and effectively, in a way that meets all the clauses, is, above all, due to not finding qualified labor and labor in the market, at all levels of construction, starting with the technical team and up to the executive staff. For that, a bibliographic review of the literature was carried out, searching in course conclusion works, articles, and specialized magazines on civil construction. Authors such as Santos and Hippert (2016), Cordovil (2013), Gil (2017), Litwinczik (2016), Britz (2018), Akkerman, Pierrard and Chrischon (2022), among others, were cited throughout the article to support the research.